2019
DOI: 10.1021/acsapm.9b00763
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Partially Fluorinated Bottlebrush Polymers in Thin Films

Abstract: We performed multiscale molecular dynamics (MD) simulations of bottlebrush polymers with fluorinated side chains to investigate the influence of the bottlebrush architecture on the spatial distribution of fluorinated moieties. In thin films, coarse-grained MD simulations reveal that interfaces are characterized by backbone depletion with side chains at the interface oriented parallel to the surface. At the molecular level, atomistic MD simulations show that fluorine atoms in the bottlebrush are preferentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
(97 reference statements)
5
12
0
Order By: Relevance
“…This physical picture is in line with current and previous MD simulations. 25 Based on these observations, one would expect to see a much larger range of orientational angles for the −OCH 2 groups, which is indeed observed and tabulated in Table 2. Notably, the orientational angles for the −OCH 2 group span a range from 32.5°± 11.5°to 78.75°± 10.75°for the linear and bottlebrush polymers, qualitatively indicating that the topmost layer, i.e., the air exposed functional groups, for the polymers is different from a structural perspective but is chemically terminated with the same species.…”
Section: ( )Cos ( )Cos ( )Cossupporting
confidence: 60%
See 2 more Smart Citations
“…This physical picture is in line with current and previous MD simulations. 25 Based on these observations, one would expect to see a much larger range of orientational angles for the −OCH 2 groups, which is indeed observed and tabulated in Table 2. Notably, the orientational angles for the −OCH 2 group span a range from 32.5°± 11.5°to 78.75°± 10.75°for the linear and bottlebrush polymers, qualitatively indicating that the topmost layer, i.e., the air exposed functional groups, for the polymers is different from a structural perspective but is chemically terminated with the same species.…”
Section: ( )Cos ( )Cos ( )Cossupporting
confidence: 60%
“…This is consistent with contact angle measurements recently reported that show similar wetting for polymer samples; only for very small oligomers are changes in the energies predicted. 25 This makes sense since the fluorinated side chains are preferentially arranged at the surface, which then forces the −CH 3 groups attached to the methacrylate chain to align more parallel to the interface, which is observed in the orientational angles measured by SFG.…”
Section: ( )Cos ( )Cos ( )Cosmentioning
confidence: 99%
See 1 more Smart Citation
“…σ S of the PTFEM coating was close to the σ S values of PTFEM coatings reported in the literature (20-22 mJ m −2 ). [130,131] The σ S of PTFEM, PL, and PH coatings were in the range of 20-25 mJ m −2 , which is considered as a surface energy yielding a minimal adhesion between biofouling and material surfaces. [132,133] After 15 days, PL and PH coatings were less fouled compared with PTFEM and PMMA coatings.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] As such, research has primarily been focused on characterization of copolymers and polymer blends using ToF-SIMS. [6][7][8][9][10][11] ToF-SIMS has been used to investigate surface chemistry, interfaces, microscopic phases, and to quantitatively map surface specific polymers in blends including styrene-methyl methacrylate random copolymers, ethylene-propylene-diene terpolymers, and polypropylene/ethylene-propylene copolymer blends [12][13][14][15] as well as to determine the molecular weight for a variety of polymers including PE, PP, and polystyrene (PS). 16 The possibility to analyze and distinguish polymers in a blend with nanosized structures becomes increasingly important as properties and performance of such materials can depend on the interfacial segregation, phase separation, and phase coarsening, which can vary in size down to tens of nanometers.…”
Section: Introductionmentioning
confidence: 99%